COMPARISON OF SPINAL CORD NEUROMODULATION OUTCOMES FOR REFRACTORY CHRONIC PAIN IN PATIENTS WITH DIABETIC NEUROPATHY AND POSTHERPETIC NEURALGIA A TECHNICAL AND QUALITY OF LIFE ANALYSIS - Alana Moury Fernandes Leite da Silva; Fernando Antônio Ferreira de Andrade Júnior; Marina Borba Vanderlei de Souza; João Victor Almeida Bonavides; Maria de Jesus Amâncio Bezerra Santos; Vitória Silva César de Albuquerque; Ray José da Silva Pires; Henrique Massao Matsumoto; Maria Eduarda Ribeiro Bernardes Lima; Pablo Ribeiro Carneiro Leão; Anita Maria Nogueira Sarmento; Paulo Victor de Albuquerque Coelho; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Considering the prevalence and debilitating nature of chronic neuropathic pain, particularly in patients with diabetic neuropathy and postherpetic neuralgia, managing this condition remains a significant clinical challenge. This study aims to evaluate the effectiveness of spinal cord stimulation (SCS) as an alternative treatment for patients refractory to conventional therapies. To this end, a review of clinical trials and case studies on SCS for chronic neuropathic pain was conducted, with a focus on pain relief and quality of life improvements. The results reveal that SCS, especially high-frequency and dorsal root ganglion neurostimulation, offers substantial pain reduction and enhanced quality of life for patients with painful diabetic neuropathy, with up to 76% pain relief in some cases. Additionally, while SCS is effective in many cases of postherpetic neuralgia, results are more variable, with some patients achieving limited relief. These findings allow the conclusion that SCS is a promising therapeutic intervention for refractory neuropathic pain, particularly when conventional pharmacological treatments fail. However, accessibility to SCS remains a barrier, underscoring the need for increased availability of this technology to enhance pain management outcomes.